Adobe Premiere Pro CC - Harrington, Richard (Classroom in a book, 2014)
The fastest, easiest, most comprehensive way to learn Adobe Premiere Pro CC Classroom in a Book®, the best-selling series of hands-on software training workbooks, offers what no other book or training program does-an official training series from Adobe Systems Incorporated, developed with the support of Adobe product experts. Adobe Premiere Pro CC Classroom in a Book contains 19 lessons that cover the basics, providing countless tips and techniques to help you become more productive with the program. You can follow the book from start to finish or choose only those lessons that interest you.